2020
DOI: 10.3390/jfmk5040100
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Physical Load on Dynamic Postural Control—A Systematic Replication Study

Abstract: Dynamic postural control is challenged during many actions in sport such as when landing or cutting. A decrease of dynamic postural control is one possible risk factor for non-contact injuries. Moreover, these injuries mainly occur under loading conditions. Hence, to assess an athlete’s injury risk properly, it is essential to know how dynamic postural control is influenced by physical load. Therefore, the study’s objective was to examine the influence of maximal anaerobic load on dynamic postural control. Six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Additionally, an investigation of risk factors and inter-limb asymmetries under loaded conditions can provide further information on an athlete’s potential injury risk since injuries mainly occur in loaded situations, e.g., during matches, competition, or training ( Bourne et al, 2019 ; Verschueren et al, 2020 ). Recently, several studies investigated the influence of load on dynamic postural control ( Wright et al, 2013 ; Johnston et al, 2018 ; Heil et al, 2020b ). Nevertheless, up to now, only one study investigated the influence of a physical loading protocol on inter-limb asymmetries in dynamic postural control.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, an investigation of risk factors and inter-limb asymmetries under loaded conditions can provide further information on an athlete’s potential injury risk since injuries mainly occur in loaded situations, e.g., during matches, competition, or training ( Bourne et al, 2019 ; Verschueren et al, 2020 ). Recently, several studies investigated the influence of load on dynamic postural control ( Wright et al, 2013 ; Johnston et al, 2018 ; Heil et al, 2020b ). Nevertheless, up to now, only one study investigated the influence of a physical loading protocol on inter-limb asymmetries in dynamic postural control.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two different types of load were compared because several studies regarding the influence of load on dynamic postural control and inter-limb asymmetries have shown that the changes seem to depend on the implemented load type and protocol ( Wright et al, 2013 ; Heil et al, 2020a ; Verschueren et al, 2020 ). Furthermore, studies often use cycling protocols ( Johnston et al, 2018 ; Heil et al, 2020b ; Verschueren et al, 2021 ), although running protocols seem to be the better choice because they are closer to the real sporting conditions. Therefore, a commonly used cycling protocol was compared to a comparable running protocol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, sincenoself-reportmeasureoffatiguewasused, studies cannot evaluate if a certain physical load caused fatigue or not (Enoka & Duchateau, 2016). dynamic postural control, several studies showed a negative effect of different types of load-e.g., cycling (Heil, Schulte, & Büsch, 2020b;Johnston et al, 2018), running (Wright et al, 2013), a high-intensity, intermittent exercise protocol (HIIP) (Whyte et al, 2015), functional protocols (Sarshin, Mohammadi, Shahrabad, & Sedighi, 2011), or local loading protocols (Gribble, Robinson, Hertel, & Denegar, 2009)-on dynamic postural control. This might be due to the former prescribed load-induced physiological alterations that also affect systems involved in the maintenance of dynamic postural control, e.g., proprioception, vision, and the vestibular system (Güler et al, 2020).…”
Section: Physical Load and Injury Riskmentioning
confidence: 99%